Implementation of Strategies to Improve Human Papillomavirus Vaccine Coverage: A Provider Survey - Walling, Emily B. (Am J Prev Med, 2019)
INTRODUCTION: Human papillomavirus (HPV) vaccine coverage in the U.S. is persistently suboptimal, despite research describing barriers to vaccination and strategies to increase vaccination coverage. The objective was to assess providers’ approach to the HPV vaccine and their implementation of strategies to increase HPV vaccination coverage. The hypothesis was that adoption of improvement measures to address underuse of the HPV vaccine has not occurred. METHODS: Community pediatric providers from two Midwestern practice-based research networks completed self-administered electronic surveys. Data were collected over 6 months in 2015 and organized and analyzed in 2016. RESULTS: There were 100 providers that participated. Despite agreement with national recommendations, some providers delayed their recommendation until the adolescent was older and many reported missed vaccination opportunities. Many providers experienced parental concerns including safety of the HPV vaccine, belief their child was not at risk of HPV infection, and their child’s resistance to receiving multiple shots. Providers identified the following as barriers to adherence to Advisory Committee on Immunization Practices guidelines: bad publicity of the HPV vaccine, information about the HPV vaccine on the web, and a lack of a follow-up system for those who delayed HPV vaccine initiation. Approximately half of the participants had implemented strategies to address these barriers beyond offering immunization only appointments. CONCLUSIONS: Participants were aware of barriers to HPV vaccine use, but many had not adopted a systematic approach to increase vaccine coverage. A better understanding of the challenges facing providers to adopting improvement measures and a strategy to address barriers to implementation are needed to improve HPV coverage.